ASPEK EKONOMI DAN SOSIAL - M Fuad Munawirsyah Nasution; Rahmad Raihan Munthe (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Social and economic aspects are closely interconnected and influence societal development. This study analyzes the impact of various policies and development practices on social and economic welfare. Using a descriptive approach through literature studies, the research explores patterns and relationships between investment, infrastructure, and community participation. Findings indicate that inclusive and sustainable economic development requires investments in education, health, and social infrastructure. Furthermore, community involvement in decision-making processes enhances policy effectiveness. This study contributes to identifying opportunities and challenges in creating an environment that supports equitable social and economic growth.